Identifikasi Faktor-Faktor Keterlambatan pada Proyek Konstruksi Repetitif Menggunakan Pendekatan Systematic Literature Review - Lando Tambunan; Defri Aryanto; Anita Setyowati Srie Gunarti; Anasya Arsita Laksmi (Journal of Sustainable Civil Engineering (JOSCE), 2026)
This study identifies and analyzes delay factors specifically in repetitive construction projects, such as roads, high-rise buildings, and housing. Using the Systematic Literature Review (SLR) method via Publish or Perish (Google Scholar, ResearchGate, ScienceDirect), an initial pool of 1,674 studies was filtered down through systematic identification, screening, and eligibility stages to a final sample of 100 accredited articles (2015–2024). Thematic analysis categorized 53 identified delay factors into six main groups , with contractor-related issues emerging as the most dominant contributor (17 factors). The top three individual factors are material and equipment impacts (43%), delayed progress payments by owners (40%), and ineffective planning and scheduling (37%). Managing contractor operations and maintaining stable owner cash flows are critical to mitigating these delays. This study provides a foundational framework for stakeholders to enhance project efficiency in repetitive construction.